Management of Herders-Farmers Conflicts in Benue State: Towards Enhancing Food Security and Agricultural Development, 2015–2026 - Emmanuel Ameh (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examines the management of herders-farmers conflicts in Benue State, Nigeria, and its implications for food security and agricultural development between 2015 and 2026. Persistent violent clashes over land, water, and grazing resources have continued to undermine Benue State’s position as the “food basket of the nation.” Despite several policy interventions, including the Benue State Open Grazing Prohibition and Ranches Establishment Law of 2017, the crisis has persisted with devastating socio-economic consequences. The study was guided by two objectives: to examine the predisposing factors responsible for herders-farmers conflicts in Benue State and to analyse the effects of the conflicts on food security and agricultural development. The study adopted a descriptive qualitative survey design. Primary data were obtained through questionnaires and interviews administered to 395 respondents selected from twelve Local Government Areas across the three senatorial districts of Benue State. Secondary data were sourced from journals, books, reports, and policy documents. The Resource Curse Theory provided the theoretical foundation of the study. Findings revealed that destruction of farmlands by herders, competition over land and water resources, infiltration of foreign pastoralists, and weak governance structures constitute the major causes of the conflicts. The study further revealed that the conflicts have negatively affected food security through destruction of crops, displacement of farming communities, reduction in agricultural productivity, and increase in food prices. In terms of agricultural development, government attention has shifted significantly from agricultural investment to crisis management and security operations. The study concludes that herders-farmers conflicts in Benue State are multidimensional and deeply rooted in environmental pressures, governance failures, and institutional weaknesses. The study recommends comprehensive reform of land-use governance and greater integration of traditional institutions into community-based conflict management frameworks.